2022
DOI: 10.1111/cns.13840
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy comparison of oxcarbazepine and levetiracetam monotherapy among patients with newly diagnosed focal epilepsy in China: A multicenter, open‐label, randomized study

Abstract: Aims This multicenter, open‐label, randomized study (Registration No. ChiCTR‐OCH‐14004528) aimed to compare the efficacy and effects of oxcarbazepine (OXC) with levetiracetam (LEV) as monotherapies on patient quality of life and mental health for patients with newly diagnosed focal epilepsy from China. Methods Patients with newly diagnosed focal epilepsy who had experienced 2 or more unprovoked seizures at greater than a 24‐h interval during the previous year were recruited. Participants were randomly assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…The detailed demographic and study characteristics are shown in Table 1. Two RCTs included in our study were open‐label studies published in 2017 and 2022 (Kim et al., 2017; Zhu et al., 2022). In both trials, enrolled participants were older than 18 years with newly diagnosed focal epilepsy according to the International League against Epilepsy's Classification of Epileptic Seizures (Fisher et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The detailed demographic and study characteristics are shown in Table 1. Two RCTs included in our study were open‐label studies published in 2017 and 2022 (Kim et al., 2017; Zhu et al., 2022). In both trials, enrolled participants were older than 18 years with newly diagnosed focal epilepsy according to the International League against Epilepsy's Classification of Epileptic Seizures (Fisher et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…There were zero fatal cases in both trials due to study medication. Only a few serious AEs were observed in one trial (Kim et al., 2017) while others had no serious AEs (Zhu et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations